The Influence of Mindfulness on the Decreasing Anxiety in Nursing Students to Support Academic Learning: A Literature Review - Reza Indra Wiguna; Meidiana Dwidiyanti; Sri Padma Sari (Holistic Nursing and Health Science, 2018)
Background: Anxiety and stress in nursing students has been shown to result in a lack of concentration, reduced learning productivity, and unfavorable physiological effects. This can cause a bad risk to the academic process of nursing students. A positive coping mechanism to reduce anxiety can be performed through various mindfulness training to support the academic success of nursing students.Purpose: This literature review study aimed to describe the influence of mindfulness on decreasing anxiety in nursing students to support academic learning, from various literature studies. Method: This study is a literature review. Data were collected through the online databases of EBSCO, PubMed, and ScienceDirect. The articles used in this study were determined published in 2010 to 2017. The key words used in searching for the articles were mindfulness, mindfulness in nursing students, nursing student anxiety, and nursing student achievement.Results: The results of this literature indicate that mindfulness is a holistic intervention that significantly improves mental health in nursing students. It can support students’  learning productivity to improve their academic achievement. The focus of mindfulness training program is to develop a better way to observe and concentrate, which in turn will facilitate a reduction in suffering and increased inner peace. Mindfulness will create relaxed attitudes and facilitates an open acceptance of experiences, thoughts, and learning.Conclusion: Mindfulness therapy with various types of exercises would be a good alternative for nursing students to reduce anxiety. Future studies should explore the long-term effects of mindfulness on the students’ learning productivity and academic achievement